PENGARUH PRESTASI KERJA DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK MANDIRI TBK KANTOR CABANG BANDAR LAMPUNG - Muhammad Aldaman; Luis Marnisah; Mohd. Kurniawan (Universitas Indo Global Mandiri)
This study aims to determine how much influence of job performance and promotion of office to job satisfaction employees at PT. Bank Mandiri Branch of Bandar Lampung, The population in this study was taken randomly from all employees of PT. Bank Mandiri Branch Office Bandar Lampung. The sample was determined by using slovin formula and obtained as many as 98 respondents. In the process of data collection, used the way interviews, questionnaires, and documentation. The research analyzes used validity analysis, reliability analysis and regression analysis using SPSS version 13 computer program. Based on the results of research known the effect on employee job satisfaction. The significant result proves that Job achievement and promotion positively influence partially and simultaneously to employee job satisfaction, where work performance becomes the most influential variable in this research. Keywords: Job performance, Job Promotion, and Job Satisfaction